21. Pelatihan Penggunaan Aplikasi Menggambar Teknik Berbasis Cad Dalam Meningkatkan Kompetensi Dasar Guru SMK Di Provinsi Banten - Abdullah, Syarif; Caturwati , Ni Ketut; Ula, Shofiatul; Rosyadi , Imron; Wiyono , Slamet; Listijorini , Erny; Saefuloh , Iman; Yusuf , Yusvardi; Jannah, Miftahul (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
One of the basic competencies that Vocational High School (SMK) mechanical engineering teachers must have is being able to draw technically using CAD (Computer Aided Design) based applications. This competency is part of the competency field of study expertise that teachers must have. From the results of observations in the field, it was found that there are still many vocational school teachers in Cilegon City who are still not experts in using CAD-based applications, one of which is SMKS YP Fatahillah 1 Cilegon. As a form of implementation of one of the duties and obligations of the Tri Dharma of Higher Education, the Mechanical Engineering Department of Sultan Ageng Tirtayasa University carries out a community service program, namely training in the use of CAD-based technical drawing applications at SMKS YP Fatahillah 1 Cilegon. This activity was carried out for 3 days and was attended by 24 participants who work as teachers and laboratory assistants at the vocational school. The training method is delivered by lectures, presentations and direct exercises and practice. From this activity, the results showed that there was an increase in the competency of the participants, namely in their ability to draw techniques.